Nature of Job and Job Satisfaction of Extension Officers in Development Agencies in Selangor and Federal Territory - Sulaiman, Ramlah (1984)
The purpose of the study was to identify and analyze the nature of job, satisfaction level, attitudes and factors of motivation of extension officers from ten agricultural development agencies in the State of Selangor and Federal Territory. Data were provided by 126 respondents who were Divisions A and B officers from the Community Development Division of the Ministry of National and Rural Development (KEMAS), Department of Agriculture, Department of Fisheries, Department of Veterinary Services, Farmers' Organization Authority (FOA), Federal Agricultural Marketing Authority (FAMA), Federal Land Development Authority (FELDA), Rubber Research Institute of Malaysia (RRIM), Rubber Industry Smallholders Development Authority (RISDA) and Universiti Pertanian Malaysia (UPM). The research was carried out from January until March, 1983.